2007
DOI: 10.1002/cncr.22560
|View full text |Cite
|
Sign up to set email alerts
|

Late toxicity and biochemical recurrence after external‐beam radiotherapy combined with permanent‐source prostate brachytherapy

Abstract: BACKGROUND The combination of external‐beam radiotherapy and brachytherapy is used commonly to treat men with prostate cancer. In this analysis, the authors examined the rate of biochemical recurrence (BR) and late grade ≥3 genitourinary (GU) and gastrointestinal (GI) toxicity after treatment with external‐beam radiotherapy and brachytherapy in a multiinstitutional, cooperative group setting. METHODS All eligible patients received external‐beam radiotherapy (45 Gray [Gy] in 25 fractions) followed 2 to 6 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…It is reassuring the overall frequency and severity of the reported AE was low, and it are comparable to other prospective brachytherapy studies. (6,(21)(22)(23) This is also comparable to other prospective HDR brachytherapy studies. Borghede et al reported on the results of 50 patients treated with 50 Gy of external beam radiotherapy combined with 2 HDR brachytherapy implants delivering a total dose of 20 Gy (2 fractions).…”
Section: Discussionsupporting
confidence: 84%
“…It is reassuring the overall frequency and severity of the reported AE was low, and it are comparable to other prospective brachytherapy studies. (6,(21)(22)(23) This is also comparable to other prospective HDR brachytherapy studies. Borghede et al reported on the results of 50 patients treated with 50 Gy of external beam radiotherapy combined with 2 HDR brachytherapy implants delivering a total dose of 20 Gy (2 fractions).…”
Section: Discussionsupporting
confidence: 84%
“…Notably, three-dimensional conformal radiotherapy techniques, including intensity-modulated radiotherapy, may not reduce late intestinal toxicity because margins around the cancer may not be able to be safely reduced and because of the prescription of higher radiation doses [97,98] . Brachytherapy, alone or as a supplement to external beam radiotherapy, is now increasingly being utilized to decrease normal tissue toxicity, without compromising treatment efficacy, in the management of prostate carcinoma [99,100] . Brachytherapy is a kind of radiotherapy whereby the source of radiation is located either within the malignant tissue (interstitial brachytherapy) or within a cavity in its immediate vicinity (intracavitary brachytherapy), rather than at a distance (typically 100 cm) from the center of the neoplasm target, as it is the case with external beam radiotherapy.…”
Section: Prevention Of Radiation Colitismentioning
confidence: 99%
“…For intermediate-and highrisk prostate cancer, brachytherapy is often combined with external beam radiation therapy (EBRT) to supplement dose to other tissues at risk, including the seminal vesicles. However, supplemental EBRT has not been uniformly supported as a means to improve disease control (3,4) and may also increase the risk of late toxicity compared with brachytherapy as monotherapy (5).…”
Section: Introductionmentioning
confidence: 99%